2014
DOI: 10.1371/journal.pone.0101984
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Promotes Wound Healing in the Oral Mucosa

Abstract: IntroductionLeptin, a 16 kDa circulating anti-obesity hormone, exhibits many physiological properties. Recently, leptin was isolated from saliva; however, its function in the oral cavity is still unclear. In this study, we investigated the physiological role of leptin in the oral cavity by focusing on its effect on wound healing in the oral mucosa.MethodsImmunohistochemical analysis was used to examine the expression of the leptin receptor (Ob-R) in human/rabbit oral mucosa. To investigate the effect of leptin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
2
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 43 publications
1
32
2
3
Order By: Relevance
“…The histatin 1 in saliva also stimulates the migration of epithelial cells and fibroblasts, 124 which facilitates the closure of wounds. More recently, Umeki et al, 125 showed that leptin, an anti-obesity hormone present in saliva, 126 promotes wound healing by stimulating angiogenesis.…”
Section: Wound-healing Factorsmentioning
confidence: 99%
“…The histatin 1 in saliva also stimulates the migration of epithelial cells and fibroblasts, 124 which facilitates the closure of wounds. More recently, Umeki et al, 125 showed that leptin, an anti-obesity hormone present in saliva, 126 promotes wound healing by stimulating angiogenesis.…”
Section: Wound-healing Factorsmentioning
confidence: 99%
“…El mantenimiento de la integridad de la mucosa oral es críticamente importante, no sólo para la función oral sino también para la salud general (Umeki et al, 2014), por lo cual la utilización de distintos compuestos de origen herbal que aceleren la reparación de los tejidos orales, se presenta como una alternativa válida hoy en día.…”
Section: Discussionunclassified
“…Leptinin yara iyileşmesindeki rolü yapılan bir çok çalışma ile ortaya konulmuştur (12)(13)(14). Lokal leptin sentezi ve sekresyonun derideki bir yaralanmanın sonrasında yükseldiği ve leptin eksikliği olan hayvanlarda yara iyileşmesinin bozulduğu ve geciktiği de gösterilmiştir.…”
Section: Yara İyileşmesiunclassified
“…Fakat oral mukozasında kimyasal yaralanması olan tavşanlarda topikal leptin uygulaması sonucunda epitelyum hücre migrasyonun artışı ve anjiyogenezisin sağlanması ile oral mukoza lezyonlarında yara iyileşmesinin sağlanması sürecinde leptinin topikal olarak tedavide kullanılabileceği bildirilmiştir (12).…”
Section: Yara İyileşmesiunclassified